(untitled) (Географический вестник=Geographical bulletin, 2017)
Исследованы особенности пространственного и сезонного распределения температуры воздуха в Республике Тыва. Анализ выполнен по данным 10 метеостанций с учетом их местоположения и своеобразия форм рельефа. Показано, что пространственное распределение приземной температуры воздуха в различные сезоны года в значительной степени определяется рельефом; другие факторы, например широта, влияют в меньшей степени. FEATURES OF EXTENSIONAL AND SEASONAL CHANGE OF TEMPERATURE OF AIR AT REPUBLIC TYVA The analysis and ordering of an available initial information of numbers of temperature of air on 10 meteorological stations of republic Tyva for the periods 1949-2008 and 1964-2002 is lead. The analysis of features of forms of a relief in view of a site of meteorological stations is given. The basic features of spatial change of temperature of air on seasons and as a whole for a year for, intermountain hollow and mountain meteorological stations are investigated. The average monthly and annual values calculated for the 60-years period, are accepted as norm. Influence of a complex relief of republic on temperature of air is shown. For example, infringement of zone distribution of average monthly temperatures of air is revealed. Comparison of a temperature mode of meteorological stations of various type has shown, that in one cases the temperature of air is defined by height of a place, in others – conditions of an arrangement of meteorological stations concerning ranges.